Optimally Tuned Interleaved Luo Converter for PV Array Fed BLDC Motor Driven Centrifugal Pumps Using Whale Optimization Algorithm—A Resilient Solution for Powering Agricultural Loads - Jegha, A. Darcy Gnana; Subathra, M.S.P.; Kumar, Nallapaneni Manoj; Ghosh, Aritra (Electronics (Basel), 2020)
The use of brushless direct current (BLDC) motors are gaining much prominence in water pumping systems (WPS), especially for agricultural purposes. In most cases, the BLDC based WPS is powered using electricity from the grid, which is vulnerable to disruptive events causing a resilience problem. However, to avoid the resilience issue, grid-interactive solar photovoltaics (PV) are being used, and this is due to the increased penetration of distributed generation sources into the grid. In these systems, based on the inherent nature of solar PV, power converters are preferred, and as a result, problems like switching losses and maintaining steady-state voltages are commonly seen. In this paper, a framework of PV powered WPS with scope for optimizing controller parameters is proposed to avoid the above-raised issues. Based on the proposed framework, the overall structure of the PV powered WPS is modeled, designed, and analyzed. In the proposed system, the power output from solar PV is fed to the BLDC motor and the grid. If any problem arises in obtaining the power from solar PV, grid-interaction helps to run the motor at required speeds making the WPS resilient to unexpected disruptions and vice versa. For retrieving the generated power from PV array, a positive interleaved Luo converter (I-Luo) is used, which boosts the output with minimum switching losses. To maintain the steady-state voltage at the output of the I-Luo converter, a proportional-integral (PI) controller whose parameters are tuned by whale optimization algorithm (WOA) is used. This voltage is fetched to the BLDC motor via a 3-phase (3-Ф) inverter and then to the grid via a single-phase (1-Ф) inverter. The overall system is simulated and experimentally validated, with a detailed analysis of the observed results. The results include the various performance characteristics of the solar PV, converter, and BLDC motor. Besides, by using the field-programmable gate array (FPGA) based SPARTAN6E controller, the performance of the I-Luo is examined experimentally.